Portrayals of Power in Suzanne Collins’ The Hunger Games and Veronica Roth’s Divergent Novels - Wandansari, Rifky Aulia; Suryaningtyas, Valentina Widya (Allure Journal, 2022)
Abstract. This research aims to compare power aspects portrayed by the main character in The Hunger Games and Divergent novels and see the similarities and differences between those two novels. The object of this research is Suzanne Collins’ The Hunger Games and Veronica Roth’s Divergent Novels. The researcher uses descriptive qualitative as the method of the study. The researcher used Karlberg's (2005) theory to conduct this research. The researcher classified the characteristic of power into Power as Domination (there are 5 types) and Power as Capacity (there are 4 types) to get the data. The other elements that help the researcher easier to collect the data that can be compared are using the novel's intrinsic elements. The result shows Katniss (The Hunger Games) and Tris (Divergent) as the main character, they have power on some points. Some points of the power from those novels have similar portrayals such as Power as Domination in Position, Power as Domination in Knowledge, Power as Domination in Experience, Power as Domination in Gender, Power as Capacity in Anger, Power as Capacity in Bravery, and Power as Capacity in Disappointed. Few points show if those two books have different portrayals, such as the point of Power as Domination in Age and Power as Capacity in Worrying. So, based on the research and the result shown, The Hunger Games and Divergent are thought of as the same novels because some power portrayals from those novels are similar.